Immunolocalization of cathepsin D in normal and neoplastic human tissues. Issue 12 (December 1986) - Reid, W A; Valler, M J; Kay, J
Abstract : The aspartic proteinase cathepsin D was purified from human spleen and localised in various formalin fixed paraffin embedded human tissues using the peroxidase-antiperoxidase (PAP) technique. Cathepsin D was shown not only in macrophages but also in other connective tissue cells, and in epithelium. It was present in spleen (littoral cells and cells within Malpighian bodies), liver (hepatocytes and Kupffer cells), lung (alveolar macrophages and bronchial epithelium), brain (neurones), lymph nodes (histiocytes in germinal centres, sinusoid lining cells) and stomach (parietal and mucous neck cells). Cathepsin D was also found in carcinomas of bronchus, stomach, colon, kidney, breast, ovary, bladder and pancreas, both in neoplastic epithelium and in stromal cells, but was seldom present in connective tissue neoplasms. A group of malignant lymphomas also contained the enzyme within scattered cells. The distribution of cathepsin D seems to be much wider than that of the structurally related aspartic proteinases pepsin, gastricsin, and renin.